2007
DOI: 10.1207/s15327655jchn2401_1
|View full text |Cite
|
Sign up to set email alerts
|

The Health of Female Child Care Providers: Implications for Quality of Care

Abstract: The purpose of this investigation was to determine the health behaviors and perceived health status of child care providers. Health behaviors and health status were also examined in relation to caring for children and the providers' perceptions of quality child care. A researcher-developed questionnaire, adapted from Williams, Mason, and Wold (2001), was mailed to a random sample of 1,000 child care providers employed in 49 child care centers in Georgia. Results indicated that, overall, the sample was a health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Two studies found that ECE workers report clinically depressive symptoms at rates approximately two to five times greater than national averages, and another study found that the workers often feel emotionally strained and distressed, which is related in part to their work. 3,11,15 However, very few studies have examined the possible relationships between job and worksite characteristics and workers' health or health behaviors.…”
mentioning
confidence: 99%
“…Two studies found that ECE workers report clinically depressive symptoms at rates approximately two to five times greater than national averages, and another study found that the workers often feel emotionally strained and distressed, which is related in part to their work. 3,11,15 However, very few studies have examined the possible relationships between job and worksite characteristics and workers' health or health behaviors.…”
mentioning
confidence: 99%